Monumental Ghosts - Bullock, Alice (Sunstone Press Santa Fe, New Mexico, 1987)
What do the Dorsey Mansion, Fort Union, the Vietnam Memorial Chapel, Quarai, White Sands, and Coronado State Monument in New Mexico have in common? They all have ghosts connected with their histories! Alice says, ''The ghosts in this volume are all 'residents' of national or state monuments. But the ghosts in New Mexico, unlike those of say, the British Isles, are rarely vicious or frightening. They are gentle ghosts and more afraid of us, apparently, than we are of them.'' Alice Bullock shares these and other ghostly tales with us in this collection of Southwestern legends, all explained in twenty stories that include the mysterious ''Blue Lady'' of Quarai National Monument.
57032
Keywords: Ghost Stories; Southwest; Monuments -- Folklore -- New Mexico; National parks and reserves -- Folklore -- New Mexico; New Mexico